2016
DOI: 10.1007/s00277-016-2690-2
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of high risk for death in patients with follicular lymphoma receiving rituximab plus cyclophosphamide, doxorubicin, vincristine, and prednisolone in first-line chemotherapy

Abstract: Risk stratification of patients with relapsed and refractory follicular lymphoma (FL) remains challenging. Recently, much attention has been paid to the impact of early progression of disease within 2 years of diagnosis (early POD) on subsequent survival. The aim of this study was to clarify the clinical features and prognostic factors of patients with FL who experienced early POD. Data were available for 94 patients diagnosed with FL (clinical stage II-IV) who had received immunochemotherapy. Early POD was se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 29 publications
3
8
0
2
Order By: Relevance
“… have identified a subgroup of FL patients treated with chemoimmunotherapy who progressed within the first 2 years after diagnosis and who are at high risk for death after treatment. Another study has recently confirmed this data in a 7.7 years median‐follow cohort of 94 patients with FL who also received first‐line chemoimmunotherapy .…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“… have identified a subgroup of FL patients treated with chemoimmunotherapy who progressed within the first 2 years after diagnosis and who are at high risk for death after treatment. Another study has recently confirmed this data in a 7.7 years median‐follow cohort of 94 patients with FL who also received first‐line chemoimmunotherapy .…”
Section: Discussionmentioning
confidence: 64%
“…Murakami et al. also identified high LDH levels as a predictor of early death in patients treated with first‐line chemoimmunotherapy. Furthermore, only ECOG PS>1 and the fact of being rituximab‐naïve at the moment of ASCT had statistical significance in the multivariate analysis.…”
Section: Discussionmentioning
confidence: 98%
“…Follicular lymphoma patients experiencing ETF following first‐line immunochemotherapy lack optimal subsequent treatment and, therefore, ETF has been recently validated as a prognostic marker of poor survival . More recently, complete response at 30 months after ASCT in FL patients has been also described as a surrogate for OS .…”
Section: Discussionmentioning
confidence: 99%
“…Anti‐CD20 maintenance therapy prolongs remission and probably survival and has become a standard of care after first‐line therapy . Nevertheless, several studies have shown that approximately 15% to 20% of patients with FL will not respond to first‐line immunochemotherapy based on rituximab (refractoriness) or will experience early therapy failure (ETF), defined as relapse or progression within 2 years of commencing first‐line immunochemotherapy . The outcome for this subgroup of high‐risk FL patients is much worse than that of those who respond well to first‐line treatment, with reported 5‐year OS of approximately 50% versus 90% in the latter …”
Section: Introductionmentioning
confidence: 99%
“…Как до «эры ритуксимаба», так и в настоящее время у 10-15 % первичных больных ФЛ протекает нетипично -наблюдается быстрое прогрессирование, отсутствие ответа на противоопухолевое лечение первой линии, а в ряде случаев -рефрактерность, больные в сроки 1,5-2 года после установления диагноза умирают [18]. Еще приблизительно у 20 % больных лимфома рецидивирует в сроки менее чем через 2 года после начала терапии первой линии [19][20][21].…”
Section: оригинальные статьиunclassified